Effectiveness of Pregnant Woman Class in The Prevention of Pregnancy Anemia in Banyuwangi, East Java - Andriani, Yeni; Respati, Supriyadi Hari; Astirin, Okid Parama (Journal of Maternal and Child Health, 2016)
Background: In developing countries 40% of maternal mortality is associated with pregnancy anemia. Pregnancy anemia has negative effect to mothers, before, during, and after delivery. The purpose of this study was determined effectiveness of pregnant woman class in the prevention of pregnancy anemia in Banyuwangi, East Java. Subjects and Method: This was an analytical observational study with retrospective cohort design. This study was conducted at Benculuk health center, Banyuwangi, East Java. A total of 100 subjects were selected for this study by fixed exposure sampling, consisting of 50 pregnant mothers who participated pregnant woman class and 50